ANALISA PEMANFAATAN THERMOELECTRIC GENERATOR SEBAGAI PEMBANGKIT LISTRIK MENGGUNAKAN PANAS GAS BUANG KENDARAAN BERMOTOR: ANALYSIS OF THE UTILIZATION OF THERMOELECTRIC GENERATORS AS POWER PLANTS USING THE HEAT OF MOTOR VEHICLE EXHAUST GASES - Ahmad Bunaya Rifqi (Jurnal Teknik Mesin, 2025)
The growth in the number of motorized vehicles increases exhaust emissions and air pollution. Emissions Exhaust gases produce heat which is discharged into the environment. The heat potential of vehicle exhaust gas can be used as a heat source to generate electricity. One of the technologies that can convert heat into electricity with zero emissions is a Generator Thermoelectric. The experimental research is to utilize the exhaust heat of motorized vehicles and convert it into electrical energy. In this study, tests were carried out using termoelektrik TEC-12706, aluminum and heatsinks as a tool to convert heat from exhaust into electrical energy. The results showed that heatsink A has a temperature difference of 35-40°C. In addition, measurements with 6 termoelektriks produce a voltage of 1.5V, a current of 0.87A and a power of 1.2W. The results of this study show the potential to utilize vehicle exhaust heat as an environmentally friendly source of electrical energy. This can help overcome the problem of exhaust emissions and air pollution caused by motorized vehicles.